Ubiquitin E3 ligase Itch negatively regulates osteoblast function by promoting proteasome degradation of osteogenic proteins. Issue 3 (March 2017) - Liu, J.; Li, X.; Zhang, H.; Gu, R.; Wang, Z.; Gao, Z.; Xing, L.
Abstract : Objectives: Ubiquitin E3 ligase-mediated protein degradation regulates osteoblast function. Itch, an E3 ligase, affects numerous cell functions by regulating ubiquitination and proteasomal degradation of related proteins. However, the Itch-related cellular and molecular mechanisms by which osteoblast differentiation and function are elevated during bone fracture repair are as yet unknown. Methods: We examined the expression levels of E3 ligases and NF-κB members in callus samples during bone fracture repair by quantitative polymerase chain reaction (qPCR) and the total amount of ubiquitinated proteins by Western blot analysis in wild-type (WT) mice. The expression levels of osteoblast-associated genes in fracture callus from Itch knockout (KO) mice and their WT littermates were examined by qPCR. The effect of NF-κB on Itch expression in C2C12 osteoblast cells was determined by a chromatin immunoprecipitation (ChIP) assay. Results: The expression levels of WW Domain Containing E3 Ubiquitin Protein Ligase 1 (Wwp1), SMAD Specific E3 Ubiquitin Protein Ligase 1 (Smurf1), SMAD Specific E3 Ubiquitin Protein Ligase 2 (Smurf2) and Itch were all significantly increased in the fracture callus of WT mice, which was associated with elevated expression of NF-κB members and total ubiquitinated proteins. Callus tissue isolated from Itch KO mice expressed higher levels of osteoblast-associated genes, including Runx2, a positive regulator of osteoblast differentiation, but osteoclast-associated genes were not increased. Both NF-κB RelA and RelB proteins were found to bind to the NF-κB binding site in the mouse Itch promoter. Conclusions: Our findings indicate that Itch depletion may have a strong positive effect on osteoblast differentiation in fracture callus. Thus, ubiquitin E3 ligase Itch could be a potential target for enhancing bone fracture healing. Cite this article: J. Liu, X. Li, H. Zhang, R. Gu, Z. Wang, Z. Gao, L. Xing. Ubiquitin E3 ligase Itch negatively regulates osteoblast function by promoting proteasome degradation of osteogenic proteins. Bone Joint Res 2017;6:154–161. DOI: 10.1302/2046-3758.63.BJR-2016-0237.R1.